Net Interest Margin and Capital Adequacy Ratio: Mediating Influence of Return on Asset - Wahyudin, Agus; Kiswanto, Kiswanto; Nuhaaya, Ailin (Jurnal Dinamika Akuntansi, 2021)
Purpose: The objectives of this study are to analyze the effect of liquidity, credit risk, and operating efficiency on bank profitability as proxied by Return on Assets and analyze the role of Net Interest Margin (NIM) and Capital Adequacy Ratio (CAR) as an intervening variable.Method: The population in this study was banking companies listed on the Indonesia Stock Ex- change (IDX) for 2015-2019. The sampling technique used the purposive sampling technique with 37 companies and 167 analysis units. The data analysis in this study used multiple linear regression analysis and path analysis.Finding: The results show that liquidity and operating efficiency significantly affect profitability. Credit risk has a significant negative effect on profitability, and NIM and CAR have a significant positive effect on profitability. Liquidity has a significant positive effect on NIM and CAR. Credit risk has an insignificant negative effect on NIM, but a significant positive on CAR, while operational efficiency has a significant negative effect on NIM. Meanwhile, NIM and CAR can only mediate liquidity to profitability, and otherwise, CAR can be mediating credit risk to profitability.Novelty: NIM and CAR can be mediate the effect of liquidity on profitability, and in particular, CAR mediates market risk on profitability. Therefore, investors should pay attention to financial banking ratios so that they do not fail in making investments.